Association of 12204590 polymorphism with the development of acute cerebrovascular event. (14th October 2021) - Chernova, A; Nikulina, S; Nikulin, D
Abstract: Purpose: To study SNP rs12204590 (T > A) with development of Acute Cerebrovascular Event in the patients with cardiovascular pathology and risk factors of its development who are representatives of the east Siberian population. Material and methods: 260 patients with Acute Cerebrovascular Event participated in a research (age [57.0; 51.0–62.0]) and 272 patients of control group (age [55.0; 51.0–62.0].). Among the patients who transferred Acute Cerebrovascular Event, 157 men and 103 women. The control group included 170 men and 102 women. Inspection of the main group included: collecting complaints, anamnesis, clinical examination, computer tomography of a brain, electrocardiography, echo, ultrasonic of arteries, daily monitoring of arterial blood pressure and cardiac rhythm, analysis of a coagulant system of blood. Patients of the main group had the following cardiovascular pathology and risk factors: arterial hypertension, supraventricular tachycardia, dislipidemiya, atherosclerosis brachiocephalic of arteries, disturbances of a system of a hemostasis. The control group is examined within the international HAPIEE project. The molecular and genetic research was conducted by PCR method in real time. Statistical processing of material was carried out with use of set of the Statistica for Windows 7.0, Excel and SPSS 22 application programs. Results: The connection of the genotype of TA SNP rs12204590 (T > A) with the development of Acute Cerebrovascular Event in a general group of patients was confirmed, but no statistically significant associations were obtained when patients were divided into subgroups depending on cardiovascular pathology and risk factors. Conclusion: The genotype of TA SNP rs12204590 (T > A), compared to the genotypes of TT and AA, reduces the risk of developing Acute Cerebrovascular Event, including in patients with arterial hypertension. The genotype of AA SNP rs12204590 (T > A) increases the risk of developing Acute Cerebrovascular Event in males. FUNDunding Acknowledgement: Type of funding sources: None.